2013
DOI: 10.1371/journal.pone.0066001
|View full text |Cite
|
Sign up to set email alerts
|

Human-Derived Physiological Heat Shock Protein 27 Complex Protects Brain after Focal Cerebral Ischemia in Mice

Abstract: Although challenging, neuroprotective therapies for ischemic stroke remain an interesting strategy for countering ischemic injury and suppressing brain tissue damage. Among potential neuroprotective molecules, heat shock protein 27 (HSP27) is a strong cell death suppressor. To assess the neuroprotective effects of HSP27 in a mouse model of transient middle cerebral artery occlusion, we purified a “physiological” HSP27 (hHSP27) from normal human lymphocytes. hHSP27 differed from recombinant HSP27 in that it for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 44 publications
4
26
0
Order By: Relevance
“…Previous studies have implicated the role of Hsp27 as a neuroprotective element in ischemic brain injuries [43], [44], [45]. Our in vitro immunocytochemical analysis shows an increase in Hsp27 concentration in rat neural cells co-cultured with DPCs compared to that of the vehicle in response to OGD conditions.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies have implicated the role of Hsp27 as a neuroprotective element in ischemic brain injuries [43], [44], [45]. Our in vitro immunocytochemical analysis shows an increase in Hsp27 concentration in rat neural cells co-cultured with DPCs compared to that of the vehicle in response to OGD conditions.…”
Section: Discussionsupporting
confidence: 50%
“…HspB1 transgenic mice showed significantly reduced cortical damage after permanent MCAO (van der Weerd et al 2010). In addition, it was shown that intravenous injection of HspB1 in mice reduced infarct volume after tMCAO (Teramoto et al 2013). Our data show that HspB1 is upregulated after tMCAO in astrocytes and in neurons indicating that it protects glial cells as well as neurons.…”
Section: Hspb1 (Hsp27)supporting
confidence: 51%
“…There is an extensive literature on the protective effects of Hsp27 in the nervous system. Overexpression of Hsp27 reduces neuronal cell death and the severity of drug-induced seizures (8), and Hsp27 injection ABBREVIATIONS: ALS, amylotrophic lateral sclerosis; CerS, ceramide synthase; CMT, Charcot-Marie-Tooth; CMT1/2/2F, Charcot-Marie-Tooth type 1/2/2F; co-IP, coimmunoprecipitation; DRG, dorsal root ganglia; ER, endoplasmic reticulum; FB1, fumonisin B1; HA, hemagglutinin; Hsp27, heat shock protein 27; IP, immunoprecipitation; KO, knockout; LC/MS, liquid chromatography/mass spectrometry; MOC, Manders' overlap coefficient; PCC, Pearson's correlation coefficient; S1P, sphingosine-1-phosphate; SIM, structured illumination microscopy; TrpV1, transient receptor potential cation channel subfamily V member 1; Tuj1, neuron-specific class III b-tubulin; WT, wild type reduces severity of sequelae of cerebral ischemia in mice (9). Hsp27 expression is upregulated in neuronal injury and thought to have a role protecting injury-induced motor neuron death (10).…”
mentioning
confidence: 99%